Rose anthocyanin microencapsulation for improving the color of two strains of koi - Soni Andriawan; Riza Rahman Hakim; David Hermawan; Choridatul Bahiyya; Ari Wahyu Darmawan; Felix Miranda; Lisma Dahlia; Arinta Agnie Dewantari (Depik, 2025)
Koi fish coloration is genetically significant, but environmental factors and color quality can lead to degradation. Some individuals use synthetic dyes to enhance their appearance, which harms the environment. This study explored the effects of microencapsulated Rose sp. flower anthocyanin (MRFA) as a natural alternative dye to enhance the color of Sanke and Kohaku koi fish. Sanke exhibits orange-black hues, while Kohaku shows orange-white hues, allowing for comparative analysis. Before the experiment, MRFA was analyzed using FESEM and XRD to assess the particle size distribution and shape of the anthocyanin microcapsules. A Randomized Complete Design (CRD) with four treatments (T0, 150 mg (T1), 300 mg (T2), and 450 mg (T3)) and five replications were used. Data was analyzed with SPSS. Results showed that MRFA particles were distributed, though not entirely homogeneous (14 m to 170 m), with XRD spectra indicating interactions between maltodextrin and Rose sp. anthocyanin. Results showed that MRFA significantly improved certain color parameters in Sanke, particularly at moderate doses (T1 and T2), but the control group (T0) outperformed MRFA in some cases. In Kohaku, no significant improvement was observed compared to the control, suggesting that MRFA was less effective in enhancing whiteorange pigmentation. Overall, our findings indicate that MRFA supported koi growth but showed limited, strain-specific effects on coloration. Further studies with longer trials and larger populations are needed to confirm its potential as a natural feed additive.Keywords:Herbal extractCyprinus carpioKohakuPigmentSanke